KAJIAN KUAT LENTUR RIGID PAVEMENT BETON FS 4.5 DENGAN PENAMBAHAN GEOGRID (TENCATE) - Riduan, M.; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
Rigid pavement is a type of road pavement that uses concrete as its main material. This study uses Biaxial Geogrid as an Addition with a pattern of one and two layers applied to the rigid pavement of Fs 4.5 Concrete This study aims to determine the Maximum Flexural Strength in FS 4.5 concrete with the addition of a Biaxial Geogrid starting from one and two layers, The method used is experimental with destructive testing on 18 samples,  This study was conducted in the Laboratory of Campus C of Bina Darma University, a block-shaped test piece measuring 15x15x30 cm, at a test age of 7 to 28 days, The results of this study showed that the use of two layers of Biaxial Geogrid increased the maximum bending strength up to 3.8 MPa at the age of 7 days and 5.1 MPa at the age of 28 days. For the value of the Maximum Flexural Strength of Normal Concrete In this study, it is 3.4 Mpa for 7 days of age 4.7 Mpa for 28 days Meanwhile, one layer of Geogrid produces a bending strength of 3.7 MPa at 7 days and 4.9 MPa at 28 days. the addition of Biaxial Geogrid increases the flexural strength of FS 4.5 concrete by 3% at 7 days and 4% at 28 days for one layer of Geogrid, as well as 6% and 9% for two layers of Geogrid Keywords: Flexural Strength of Biaxial Geogrid Concrete